A robust multicast communication protocol for Low power and Lossy networks. (15th August 2020) - Conti, Mauro; Kaliyar, Pallavi; Lal, Chhagan
Abstract: Routing Protocol for low power and Lossy networks (RPL) is a standardized routing protocol for low power and lossy networks (LLNs) such as the Internet of Things (IoT). RPL was designed to be a simple (but efficient) and practical networking protocol to perform routing in IoT networks that consists of resource constrained devices. These tiny intercommunicating devices are currently in use in a large array of IoT application services (e.g., eHealth, smart agriculture, smart grids, and home automation). However, the lack of scalability and the low data communication reliability due to faulty links or malicious nodes, still remains significant challenges in the broader adoption of RPL in LLNs. In this paper, we propose RECOUP, a robust multicast communication routing protocol for Low power and Lossy Networks. RECOUP efficiently uses a low-overhead cluster-based multicast routing technique on top of the RPL protocol. RECOUP increases the probability of message delivery to the intended destination(s), irrespective of the network size and faults (such as broken links or non-responsive nodes), and in the presence of misbehaving nodes. An implementation of RECOUP is realized in Contiki. Our results show the effectiveness of RECOUP over state-of-art protocols concerning packet delivery ratio to 25%, end-to-end delay down to 100 ms, and low radio transmissions required for per packet delivery to 6 mJ. Moreover, it minimizes the impact of various topologies (i.e., rank and sybil) and data communication (i.e., blackhole, wormhole, and jamming) attacks that targets an IoT networking infrastructure.